The Effect of the Model Contingent Teaching on Improving Iranian EFL Learners’ Writing Self-Regulation Strategies - Leila Behzadi Soufiani; Saeideh Ahangari; Mahnaz Saeidi (Iranian Evolutionary Educational Psychology Journal, 2023)
Self-regulation strategies regarding writing can be referred to as learners’ initiative and self-directed behavior to achieve several goals to foster their writing skills. Based on the three main aspects of scaffolding; contingency, fading, and the transfer of responsibility, this study aimed at delving into the effect of the model of contingent teaching on improving Iranian language learners’ writing self-regulation strategies and its components.  The participants of the study aged between 20-30 included 60 intermediate language learners from a language institute in Tabriz, Iran. The participants were selected based on convenience sampling in the form of four intact classes. Then, they were randomly assigned to two groups: the control and the experimental group. The experimental group was exposed to treatment for 18 sessions. The Questionnaire of English Writing Self-Regulated Learning Strategies (QEWSRLS) was applied to both groups before and after the treatment. The questionnaire was designed as a multifaceted model, consisting of cognition, metacognition, social behavior, and motivational factors. The results of MANCOVA analysis revealed that teaching writing by the model of contingent teaching was influential in improving EFL learners writing self-regulation strategies (F=7.36, p<0.05, Wilks’ Lambda=0.38, Eta Square=0.61). Also, the main effect was exerted on text processing (F=26.4, P<0.05, Eta Square=0.35). The study offers some practical implications for teacher trainers, teachers, and EFL learners which are discussed.